Contribution of Hepatitis C Infection to a Large Cohort of Cryoglobulin-Positive Patients: Detection and Characteristics - Kolopp-Sarda, Marie N.; Miossec, Pierre (Frontiers in Immunology, 2020)
Cryoglobulins (CGs) are cold precipitating immunoglobulins, and hepatitis C virus (HCV) infection is its most common cause. The purpose of the study was to determine the contribution of HCV in a large cohort of CG. Biological characteristics and specificity of CGs in HCV patients were compared to non-HCV subjects. Cryoglobulin analysis included isotype, clonality, concentration, and rheumatoid factor (RF) in cryoprecipitate and serum complement and RF. This study is an extension of the study carried out on a cohort of 13,439 patients tested for CGs from all medical units, in which 1,675/13,439 (12.5%) patients had a CG, and 680/1,675 (40.6%) had HCV serology or viral load determination (HCV RNA). Among these 680 CG patients tested for HCV, 325 of 680 (47.8%) HCV patients (272 HCV RNA+ and 45 HCV RNA− patients) were compared to 355/680 (52.2%) non-HCV subjects. After a positive detection of CG, HCV status was determined only for 37.7% (256/680) of patients, allowing the diagnosis of a previously unknown HCV infection for 39.8% (102/256). Concentration of HCV RNA+ CGs (median = 80.5 mg/L) was significantly higher than that of HCV RNA− CG (median = 50.5 mg/L, p = 0.001) and HCV− CG (median = 32 mg/L, p < 0.0001). There was no difference of median CG concentration between HCV RNA− patients and non-HCV subjects. Rheumatoid factor titer was significantly higher in type II CG compared to type III CG in HCV RNA+ patients (254 ± 720 vs. 15 ± 21 IU/mL, p < 0.0001) and non-HCV subjects (333 ± 968 vs. 16.8 ± 26 IU/mL, p = 0.0004). Complement functional activity CH50 was lower in HCV RNA+ patients (36 ± 24 U/mL) and in HCV RNA− patients (32 ± 21 U/mL) than in non-HCV subjects (50 ± 25 U/mL, p = 0.001 and p = 0.004). In conclusion, HCV infection and treatment influence CG characteristics. It is essential, and far from always tested, to determine the HCV status of patients with mixed CG, and conversely to search for CG in patients with HCV infection.